Insight to the molecular mechanisms of the osmolyte effects on Mycobacterium tuberculosis pyrazinamidase stability using experimental studies, molecular dynamics simulations, and free energy calculation - Mohadese Khajehzadeh; Saeedeh Khaleghnejad; Faramarz Mehrnejad; Mohammad Pazhang; Farahnoosh Doustdar (International Journal of Mycobacteriology, 2018)
Background: In this study, we have experimentally investigated the effects of different osmolytes including sucrose, sorbitol, urea, and guanidinium chloride (GdmCl) on the stability and structure of the Mycobacterium tuberculosis pyrazinamidase (PZase). PZase converts pyrazinamide to its active form. Methods: In addition, in order to gain molecular insight into the interactions between osmolytes and PZase, we have conducted 1000-ns molecular dynamics simulations. Results: The results indicated that sucrose and sorbitol increase the stability and compactness of the enzyme, whereas in the presence of urea and GdmCl, PZase loses its stability and compactness. Furthermore, the activity of PZase in the presence of sucrose was more than the other solutions. The energetic analyses imply that the electrostatic and van der Waals interactions are the major factors in the osmolyte–PZase interactions. Sorbitol and sucrose, as protective osmolytes, protect the protein structure by utilizing the van der Waals interaction from denaturation. In addition, urea molecules affect the structure of the protein using the hydrogen bonds and van der Waals interactions. Conclusion: The results show that the most important factor in the denaturing effect of GdmCl is the strong interactions of positively charged guanidinium ions with the aspartate and glutamate residues.